ASSA14-03-26 Cellular repressor of E1A stimulated genes antagonise inflammation in RAW 264.7 cells via autophagy-lysosome pathway. (1st December 2014) - Sun, M; Han, Y; Yan, C
Abstract : Background: Macrophage inflammation plays an important role in the pathogenesis of atherosclerosis. In this study, we investigated the involvement of cellular repressor of E1A-stimulated genes (CREG) in tumour necrosis factor-α (TNF-α)-induced macrophage inflammation, and explored its inhibitory capacity and mechanisms to assess its potential as a therapeutic reagent for atherosclerosis. Methods: RAW 264.7 mouse macrophage-like cells were transfected with CREG siRNA to down-regulate the expression of CREG. The expression of CREG, cathepsin B, cathepsin L, LAMP1, IGFIIR, LC3, Beclin 1, p62 and Tubulin was identified by Western blot. The amounts of IL-6 and MCP-1 secreted into the cell culture supernate and expressed in the tissue lysates were determined using ELISA kits. Colocalization of anti-His and anti-cathepsin B/ cathepsin L/ M6P/IGFIIR/ LAMP1 was determined by immunofluorescence analysis and confocal microscopy. Lysosomal visualisation was carried out using the Lysotracker Red staining. Accumulation of autophagosomes and autolysosomes were detected in CREG-treated and CREG down-regulated cells using electron microscopy. The interaction between the exogenous recombinant CREG protein and cathepsin B, cathepsin L and IGFIIR were studied with immunoprecipitation analysis. Male ApoE −/− mice (n = 40, age 10 weeks, 20–25 g) were fed a high-fat, high-cholesterol diet containing 21% fat and 1.3% cholesterol for 16 weeks. The mice underwent sham operation or were infused with CREG protein (Abcam, UK) at a rate of 30 μg/kg/d during the 4–12 weeks by an osmotic mini-pump. Aortas were collected for oil red O and hematoxylin-eosin staining to assess atherosclerotic plaques. The expression of CD68 and MCP-1 in the atherosclerotic plaques was detected by the immunohistochemical staining. Results: We confirmed that CREG played an important role in TNF-α-induced macrophage inflammation and had anti-inflammatory effects in RAW 264.7 mouse macrophages induced by TNF-α. Results of ELISA assays showed that the amount of IL-6 and MCP-1 secreted into the cell culture supernate decreased in a dose-dependent manner in the RAW 264.7 cells supplemented with exogenous recombinant CREG protein and increased in those knocking down of CREG expression by siRNA. Gain-of-function and loss-of-function experiments revealed that CREG promoted autophagy in TNF-α-induced RAW 264.7 cells. The numbers of autolysosomes increased in RAW 264.7 cells following treatment with CREG protein while less autolysosome were seen in those transfected with CREG siRNA. Meanwhile, exogenous CREG protein induced autophagy with significant increased autophagosome-bound LC3-II and Beclin 1 abundance and decreased the level of p62. Increment of LC3-II and Beclin 1 and accumulation of p62 in CREG down-regulated cells suggested accumulation of autophagosomes and impairment of autophagy. Using the autophagy inhibitors 3-methyladenine and bafilomycin A, we demonstrated that autophagy played an important role in attenuating TNF-α-induced inflammation. Immunofluorescence analysis and western blotting showed that CREG protein stimulated the expression and maturation of cathepsin B and cathepsin L and induced the biogenesis of lysosomes, while CREG deficiency reduced lysosome biogenesis. Since lysosomal activity is essential to autophagy, we deduce that CREG may mediate the regulation of autophagy via its effects on lysosomes. Exogenous CREG protein was located in lysosomes, as shown by confocal microscopy and immunoprecipitation analysis. CREG protein played a critical role in the distribution but not in the expression of mannose-6-phosphate/insulin-like growth factor II receptor (M6P/IGFIIR), as demonstrated by western blotting and immunofluorescence analysis. In vivo experiments indicated that CREG protein alleviated the development of aortic atherosclerosis and affected inflammation and autophagy in aortas of ApoE −/− mice. Haematoxylin-eosin staining showed that the aortic lesion area was significantly reduced in the CREG-treated mice compared with those in the control group. The expression of MCP-1 in arterial tissue detected by ELISA assays and CD68, a marker of active macrophages and MCP-1 in atherosclerotic lesions of aortic root sections determined by immunohistochemical staining were all decreased in CREG-treated group. Furthermore, Western analysis of aorta lysates showed increased autophagosome-bound LC3-II abundance and p62 consumption in CREG-treated group. Conclusion: CREG inhibits macrophage inflammation and promotes autophagy mediated by lysosome biogenesis, which is related to the distribution of M6P/IGFIIR. CREG may represent a new therapeutic target against atherosclerosis.